PENERAPAN MODEL ACTIVE DEBATE UNTUK PEMBELAJARAN SEJARAH KELAS X IPS DI MAN 2 LUBUKLINGGAU - Feni Selvita; Agus Susilo; Isbandiyah (LPPM Universitas Cipta Mandiri, 2024)
This research aims to describe the application of the Active Debate learning model for History Learning for Class X IPS at MAN 2 Lubuklinggau. The research method used was quasi-experimental. Data collection techniques in research use tests. Data analysis techniques with normality test steps and hypothesis testing. Based on the research results, it can be concluded that the application of the Active Debate learning model for History Learning for Class X IPS at MAN 2 Lubuklinggau. This is proven by the pre-test results with an average score of 42.19. After being given treatment by applying the Active Debate model, it was discovered that the post test results increased by 36.26 to an average value of 78.45 which was greater than the pre test calculation. After analyzing the results of the data using the t test formula, a t value of 13.76 was obtained. These results are compared with ttable at the 5% significance level, namely: tcount (13.76) ˃ ttable (2.04). So the hypothesis can be concluded that the application of the Active Debate learning model can improve the history learning outcomes of class X IPS students at MAN 2 Lubuklinggau.